2020 IEEE International Symposium on High Performance Computer Architecture (HPCA) 2020
DOI: 10.1109/hpca47549.2020.00051
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Highly Efficient Capsule Networks Processing Through A PIM-Based Architecture Design

Abstract: In recent years, the CNNs have achieved great successes in the image processing tasks, e.g., image recognition and object detection. Unfortunately, traditional CNN's classification is found to be easily misled by increasingly complex image features due to the usage of pooling operations, hence unable to preserve accurate position and pose information of the objects. To address this challenge, a novel neural network structure called Capsule Network has been proposed, which introduces equivariance through capsul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…Efficient CapsNet research is not present in the state of the art and can benefit from adding robustness and more accurate performance for face recognition in embedded systems. Early research on efficient Capsule Networks [123] has suggested that the major bottleneck is the dynamic routing procedure (which determines which capsule is a vector going to connect). This procedure is very intensive on memory calls.…”
Section: Discussion On Future Research Directionsmentioning
confidence: 99%
“…Efficient CapsNet research is not present in the state of the art and can benefit from adding robustness and more accurate performance for face recognition in embedded systems. Early research on efficient Capsule Networks [123] has suggested that the major bottleneck is the dynamic routing procedure (which determines which capsule is a vector going to connect). This procedure is very intensive on memory calls.…”
Section: Discussion On Future Research Directionsmentioning
confidence: 99%
“…Attending to the specifications of these devices we estimate that, at maximum power, these MCUs consume less than 1% of the energy consumed by NVIDIA GTX 980 Ti also at maximum power. To get a better insight into the energy 6 Related Work Zhang et al [2020] proposed a hybrid computing architecture to accelerate the routing procedure of CapsNets during inference in GPU platforms. The authors claim that even in modern GPUs, provided with highly optimized software libraries for DL tasks, CapsNets exhibit low efficiency due to their routing procedure.…”
Section: Primary Capsule and Capsule Kernelsmentioning
confidence: 99%
“…In contrast to CNNs, which are invariant to translation, combining these features makes Capsnets equivariant, understanding proportion and pose changing [El Alaoui-Elfels, Omaima and Gadi, Taoufiq, 2021]. As a consequence, CapsNets have shown promising results to solve real-life problems and outperform CNNs in astronomy [Katebi et al, 2019], autonomous cars [Dinesh Kumar, 2018, Pari S. et al, 2019, machine translation [Wang et al, 2018], healthcare [Toraman et al, 2020], and so on [Kwabena Patrick et al, 2019, Zhang et al, 2020.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ever-increasing scale and complexity of the networks with large-scale training datasets such as ImageNet-2012 [25] are bringing more and more challenges to the cost of DNN training, which requires large amounts of computations and resources such as memory, storage, and I/O [41,58,[70][71][72]. Previous works have also tried some optimization methods to try to overcome these challenges [9,10,17,26,51,59].…”
Section: Introductionmentioning
confidence: 99%